Respuesta :
4x − y = −11
2x + 3y = 5
lets multiply the second equation by -2 and add it to the first:
4x − y = −11
-4x - 6y = -10
------------------
0 - 7y = -21
y = -21/-7
y = 3
now we substitute this result in the first equation to find x:
4x − y = −11
4x - 3 = -11
4x = -8
x = -8/4
x = 2
so the solution is y = 3 and x =2
4x − 9y = −21
−10y = −30
we solve for y
−10y = −30
y = -30/-10
y = 3
and substitute in the first equation:
4x − 9y = −21
4x − 9(3) = −21
4x - 27 = -21
4x = 6
x = 6/4 = 3/2
so the solution is x = 3/2 and y = 3
4x + 3y = 5
2y = −6
we solve for y:
2y = −6
y = -6/2
y = -3
we do substitute in the first equation:
4x + 3y = 5
4x + 3(-3) = 5
4x - 9 = 5
4x = 14
x = 14/4
x = 7/2
so the solution is x = 7/2 and y = -3
7x − 3y = −11
9x = −6
we solve for x:
9x = −6
x = -6/9
x = -2/3
then we substitute in the first equation the result found:
7x − 3y = −11
7(-2/3) − 3y = −11
-14/3 - 3y = -11
we multiply by 3 to eliminate fractions:
-14 - 9y = -33
9y = 19
y = 19/9
so the solution is x = -2/3 and y = 19/9
12x − 3y = −33
14x = −28
we solve for x:
14x = −28
x = -28/14
x = -2
then we substitute in the first equation:
12x − 3y = −33
12(-2) − 3y = −33
-24 - 3y = -33
3y = 9
y = 3
then the solution is x = -2 and y = 3
2x + 3y = 5
lets multiply the second equation by -2 and add it to the first:
4x − y = −11
-4x - 6y = -10
------------------
0 - 7y = -21
y = -21/-7
y = 3
now we substitute this result in the first equation to find x:
4x − y = −11
4x - 3 = -11
4x = -8
x = -8/4
x = 2
so the solution is y = 3 and x =2
4x − 9y = −21
−10y = −30
we solve for y
−10y = −30
y = -30/-10
y = 3
and substitute in the first equation:
4x − 9y = −21
4x − 9(3) = −21
4x - 27 = -21
4x = 6
x = 6/4 = 3/2
so the solution is x = 3/2 and y = 3
4x + 3y = 5
2y = −6
we solve for y:
2y = −6
y = -6/2
y = -3
we do substitute in the first equation:
4x + 3y = 5
4x + 3(-3) = 5
4x - 9 = 5
4x = 14
x = 14/4
x = 7/2
so the solution is x = 7/2 and y = -3
7x − 3y = −11
9x = −6
we solve for x:
9x = −6
x = -6/9
x = -2/3
then we substitute in the first equation the result found:
7x − 3y = −11
7(-2/3) − 3y = −11
-14/3 - 3y = -11
we multiply by 3 to eliminate fractions:
-14 - 9y = -33
9y = 19
y = 19/9
so the solution is x = -2/3 and y = 19/9
12x − 3y = −33
14x = −28
we solve for x:
14x = −28
x = -28/14
x = -2
then we substitute in the first equation:
12x − 3y = −33
12(-2) − 3y = −33
-24 - 3y = -33
3y = 9
y = 3
then the solution is x = -2 and y = 3
4x-y=-11
2x+3y=5
Solve 4x-y=-11 for y
Add -4x to both sides
4x-y+-4x=-11+-4x
-y=-4x-11
Divide both sides by -1
-y/-1=-4x-11/-1
y=4x+11
Substitute 4x+11 for y in 2x +3y=5
2x+3y=5
2x+3(4x+11)=5
Simplify both sides of the equation
14x+33=5
Add -33 to both sides
14x+33+-33=5+-33
14x=-28
Divide both sides by 14
14x/14=-28/14
x=-2
Substitute -2 for x in y= 4x+11
y=4x+11
y=(4)(-2)+11
Simplify both sides of the equation
y=3
Let's see if D will equal the same
14x=-28
12x-3y=-33
Solve 14x =-28 for x
14x/14=-28/14
x=-2
Substitute -2 for x in 12x-3y=-33
12x-3y=-33
(12)(-2)-3y=-33
Simplify both sides of the equation
-3y-24=-33
Add 24 to both sides
-3y-24+24=-33+24
-3y=-9
Divide both sides by -3
-3y/-3=-9/-3
y=3
Answer D
x=-2 and y=3
Sorry for taking so long with it but I hope you understand , have a great night